Synthesis, spectral characterization, electrochemical and anti-microbial activities of new binuclear Schiff base metal complexes derived from 3,3’ diaminobenzedine - Jayaseelan, Poomalai; Prasad, Selladurai; Vedanayaki, Subramanian; Rajavel, Rangappan (European Journal of Chemistry, 2011)
A novel oxime ligand has been synthesized by refluxing 3,3’-diaminobenzedine and phthalaldehyde monoxime. Copper (II), cobalt (II), nickel (II) and manganese (II) binuclear complexes of this ligand have been prepared and characterized by using elemental analysis, molar conductance studies, IR, UV, NMR, EPR and magnetic studies. The molar conductance measurements correspond to a non-electrolytic nature for all complexes which can be formulated as [M2(L)X4] (Where M = Cu(II), Ni(II), Co(II) and Mn(II); X = Cl−). The UV-visible spectra of all the complexes are well characterized by broad weak d-d band and a high intensity charge-transfer transition. Thermal studies supported the chemical formation of these complexes showed that they decomposed in three or four stages depending on the type of ligand. The far-IR spectrum confirms the presence of coordinate chloride ion in all the complexes as evidenced by one intense far IR bands around 310-330 cm−1. In electrochemical studies the resulting cyclic voltammogram consists of single quasi-reversible one electron transfer. The ligand and complexes have been screened for their antimicrobial activity against two Gram-positive bacteria, two Gram-negative bacteria and fungi. The binuclear metal complexes were found to possess potent antimicrobial, antifungal activity better than ligand alone.